Ignition of bio-water-coal fuels based on coal and charcoal; Combustion Science and Technology; Vol. 194, iss. 5 - Kuznetsov G. V. Geny Vladimirovich; Malyshev D. Yu. Dmitry Yurievich; Syrodoy S. V. Semen Vladimirovich; Gutareva N. Yu. Nadezhda Yurievna; Purin M. V. Mikhail Vladimirovich; Kostoreva Zh. A. Zhanna Andreevna (2020, 2020)
Title screen